Selenium, antioxidants, cardiovascular disease, and all-cause mortality: a systematic review and meta-analysis of randomized controlled trials. Issue 6 (14th October 2020) - Jenkins, David J A; Kitts, David; Giovannucci, Edward L; Sahye-Pudaruth, Sandhya; Paquette, Melanie; Blanco Mejia, Sonia; Patel, Darshna; Kavanagh, Meaghan; Tsirakis, Tom; Kendall, Cyril W C; Pichika, Sathish C; Sievenpiper, John L
ABSTRACT: Background: Antioxidants have been promoted for cardiovascular disease (CVD) risk reduction and for the prevention of cancer. Our preliminary analysis suggested that only when selenium was present were antioxidant mixtures associated with reduced all-cause mortality. Objective: We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to determine the effect of selenium supplementation alone and of antioxidant mixtures with or without selenium on the risk of CVD, cancer, and mortality. Methods: We identified studies using the Cochrane Library, Medline, and Embase for potential CVD outcomes, cancer, and all-cause mortality following selenium supplementation alone or after antioxidant supplement mixtures with and without selenium up to June 5, 2020. RCTs of ≥24 wk were included and data were analyzed using random-effects models and classified by the Grading of Recommendations, Assessment, Development, and Evaluation approach. Results: The meta-analysis identified 9423 studies, of which 43 were used in the final analysis. Overall, no association of selenium alone or antioxidants was seen with CVD and all-cause mortality. However, a decreased risk with antioxidant mixtures was seen for CVD mortality when selenium was part of the mix (RR: 0.77; 95% CI: 0.62, 0.97; P = 0.02), with no association when selenium was absent. Similarly, when selenium was part of the antioxidant mixture, a decreased risk was seen for all-cause mortality (RR: 0.90; 95% CI: 0.82, 0.98; P = 0.02) as opposed to an increased risk when selenium was absent (RR: 1.09; 95% CI: 1.04, 1.13; P = 0.0002). Conclusion: The addition of selenium should be considered for supplements containing antioxidant mixtures if they are to be associated with CVD and all-cause mortality risk reduction. This trial was registered at https://www.crd.york.ac.uk/PROSPERO/ as CRD42019138268.